2017
DOI: 10.1016/j.visres.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

3D faces are recognized more accurately and faster than 2D faces, but with similar inversion effects

Abstract: Recognition of faces typically occurs via holistic processing where individual features are combined to provide an overall facial representation. However, when faces are inverted, there is greater reliance on featural processing where faces are recognized based on their individual features. These findings are based on a substantial number of studies using 2-dimensional (2D) faces and it is unknown whether these results can be extended to 3-dimensional (3D) faces, which have more depth information that is absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Face inversion disrupts this process leading face recognition accuracies to drastically decline when inverted faces are presented (Yin, 1969). While the vast majority of studies examined face processing in two-dimensional faces, it was recently reported that recognition is improved for 3D vs. 2D faces but not when they are inverted (Eng et al, 2017). This refined recognition is likely due to improved holistic processing when faces are more realistic and depth information is enriched.…”
Section: Discussionmentioning
confidence: 99%
“…Face inversion disrupts this process leading face recognition accuracies to drastically decline when inverted faces are presented (Yin, 1969). While the vast majority of studies examined face processing in two-dimensional faces, it was recently reported that recognition is improved for 3D vs. 2D faces but not when they are inverted (Eng et al, 2017). This refined recognition is likely due to improved holistic processing when faces are more realistic and depth information is enriched.…”
Section: Discussionmentioning
confidence: 99%
“…A three-dimensional representation allows for the display and processing of all three dimensions of a face equally and without one of them being discarded or distorted. It compensates for the lack of depth in traditional photographs, which creates difficulties for recognizing faces in a holistic manner, and reduces the ability to ascertain the topography of separate facial features (Eng et al 2017). Ultimately, given an easy conversion between 3D and 2D data, it provides a good starting point for the examination of both 3D and 2D faces and face-related processes (Ferková et al 2017).…”
Section: Extended Public Fidentis 3d Face Databasementioning
confidence: 99%
“…These studies suggest strength, weight, and height can be judged somewhat accurately from face images, but no studies have yet directly compared the effect of stimulus type (2D versus 3D face images) on the accuracy of perceptions of these (or any other) traits. While some previous work has used both 2D and 3D images, these studies have focused on testing attractiveness and formidability ratings only (Tigue et al, 2012;Trebicky et al, 2018), or similarities in face recognition (e.g., Eng et al, 2017) and morphological measurements (e.g., Hill et al, 2017).…”
Section: Introductionmentioning
confidence: 99%